Elaborate ultrastructure of the Hirudo (Annelida: Hirudinae) cocoon surface - Saidel, William M.; Saglam, Naim; Salas-de la Cruz, David; Saunders, Ralph; Shain, Daniel H. (Wiley, 2018)
Species of medicinal leeches (Hirudo medicinalis, H. verbana, and H. sulukii) secrete hard-shelled cocoons. When initially deposited, a cocoon is surrounded by a foam. Over a short time, the foam is transformed into a three-dimensional structure. We show here that this peripheral structure likely forms by the solidification and dehydration of a moderately viscous, proteinaceous substance that surrounds bubbles of various sizes. The resulting matrix-like structure comprises a network of curved branches juxtaposed at approximate to 120 degrees and taper in width as a function of distance from the outer cocoon wall. The material is proteinaceous, and traps environmental material in its composition, especially silicon. The geometry of compartments and abundance of silicon on branch surfaces suggest a mechanism for trapping water to prevent desiccation in a terrestrial environment.
Keywords: cocoon; foam; leech; SEM; X-ray